2019
DOI: 10.1002/ygh2.336
|View full text |Cite
|
Sign up to set email alerts
|

Probable neuropsychiatric toxicity of polyethylene glycol: roles of media, internet and the caregivers

Abstract: Summary Background and aim To investigate the nature, origin and extent of reported neuropsychiatric side effects of polyethylene glycol 3350 (PEG, MiraLax©) leading to avoidance of this laxative by parents and caregivers. Methods We analysed (a) Federal Drug Administration (FDA) Adverse Effect Reporting System (AERS) data. (b) Google Search© and Google Trend© analysis of internet search trends of PEG side effects and (c) Surveys of US paediatric gastroenterologists. The data was analysed by descriptive statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…This overlap has made it difficult to interpret whether neuropsychiatric symptoms in children taking PEG3350 are secondary to laxative use or naturally co‐occur with the underlying constipation. Although multiple studies have reported on the safety of PEG3350 (4–6,8,11), parents are still reluctant to use PEG3350 (38). Although we cannot rule out that laxatives affect behavior in children with chronic constipation, our study found no evidence that PEG3350 (or magnesium citrate) significantly affects anxiety‐like behavior in mice tested on standard tasks.…”
Section: Discussionmentioning
confidence: 99%
“…This overlap has made it difficult to interpret whether neuropsychiatric symptoms in children taking PEG3350 are secondary to laxative use or naturally co‐occur with the underlying constipation. Although multiple studies have reported on the safety of PEG3350 (4–6,8,11), parents are still reluctant to use PEG3350 (38). Although we cannot rule out that laxatives affect behavior in children with chronic constipation, our study found no evidence that PEG3350 (or magnesium citrate) significantly affects anxiety‐like behavior in mice tested on standard tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Although laxatives are commonly used for the management of chronic childhood constipation, there is a paucity of data addressing their efficacy, safety, and tolerability ( 7 ). The commonly used laxative polyethylene glycol has come under scrutiny, with gastrointestinal (GI) and neuropsychiatric adverse events (AEs) reported ( 8 , 9 ). Despite the chronic nature of the disease, no trials have examined the long-term benefits of drug therapy in PFC ( 7 ).…”
mentioning
confidence: 99%
“…Ключові слова: функціональний запор, діти, «Інулін-Нео». Батьки дітей із запорами бояться призначення препаратів упродовж тривалого періоду через залежність від проносних засобів чи їхні можливі побічні ефекти [2,10,18]. Таким чином, існує потреба у вивченні інших варіантів лікування у дітей із ФЗ.…”
Section: оцінка ефективності застосування інуліну при функціональному...unclassified